(untitled) (CIPEEX, 2022)
OBJECTIVE: TO REPORT THE EXPERIENCE OF A STUDENT IN THE PHYSICAL THERAPY HEALTH COURSE PARTICIPATING IN THE ACADEMIC LEAGUE OF ORTHOPEDICS, ORTHOTRAUMA, RHEUMATOLOGY, AND SPORTS (LOORS) AND THE INFLUENCE ON THE CONSTRUCTION OF A BROAD CURRICULUM BASED ON THE TRIPOD OF EDUCATION- TEACHING, RESEARCH, AND EXTENSION. EXPERIENCE REPORT: THE SELECTION PROCESS WAS CARRIED OUT IN 2017 FOR THE ENTRY OF NEW MEMBERS INTO THE LOORS LEAGUE, THE STUDENT BEING INCLUDED IN THE LEAGUE EXPERIENCES DIFFERENT EXPERIENCES IN THE CONTEXT OF TEACHING WITH FORTNIGHTLY CLASSES WITH THE THEME OF DIRECTED STUDY FOCUS, GUEST SPEAKERS WITH EVIDENCE-BASED CLINICAL PRACTICE; IN RESEARCH, IT IS THROUGH THE LEAGUE THAT THE FIRST OPPORTUNITIES FOR PARTICIPATION IN CONGRESSES, PRESENTATION OF WORKS, WRITING OF SCIENTIFIC ARTICLES WITH THE GUIDANCE OF THE RESPONSIBLE PROFESSOR ARISE; IN THE EXTENSION, THERE IS A POSSIBILITY OF DEVELOPING EXTENSION ACTIVITIES IN SEVERAL AREAS, WHETHER IN THE MONITORING OF OBSERVATIONAL INTERNSHIP, WORK WITH THE POPULATION, WORK ON THE ORIENTATION AND PREVENTION OF PATHOLOGIES. WITH ALL THIS FOUNDATION, STUDENT PARTICIPATION IS ENCOURAGED WITH SCIENTIFIC INITIATION PROJECTS, EXTENSIONS, AND A STUDY BASED ON CURRENT SCIENTIFIC EVIDENCE. STUDENTS WHO START A SCIENTIFIC CAREER IN THE LEAGUE STAND OUT IN THE JOB MARKET, AND IN THEIR ACADEMIC CAREER, PRESENTING A STANDARD CURRICULUM OF EXCELLENCE, FOLLOWED WITH ADMISSION TO THE STRICT SENSE POSTGRADUATE COURSE SUCCESSFULLY IN THE SELECTION PROCESS OF SCHOLARSHIP HOLDERS FOR THE MASTER’S MODALITY. IT IS POSSIBLE TO SUGGEST THAT PARTICIPATION IN ACADEMIC LEAGUES GENERATES STUDENTS AN EXPANSION OF THE FIELD OF ACTION AND CURRICULAR EXPANSION FOR PERSONAL AND CURRICULAR DEVELOPMENT, PROVIDING ACADEMIC SUCCESS. THE STUDENT PARTICIPATING IN A LEAGUE HAS DEVELOPED A SENSE OF RESPONSIBILITY, TIME MANAGEMENT, AND GROUP WORK RELEVANT TO A PHYSIOTHERAPIST-PATIENT RELATIONSHIP OF EXCELLENCE.